Moderasi Beragama dalam Bingkai Toleransi di Desa Namo Batang - Alfin Nurikhsan; Indah Permata Sari; Maulana Syahbanti (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2021)
This study discusses religious moderation in the frame of tolerance in the village of Namo Batang. This study emphasizes that moderation in religious harmony must be carried out, because by doing so will create inter-religious harmony or belief. This research is a type of qualitative research, the research location is in Namo Batang, Deli Serdang Regency, the village that is the location of the KKN-DR which is inhabited by several religions, namely Islam, Christianity, Protestantism, Catholicism, and Christianity . Religious tolerance is not about melting into one another's beliefs. Nor to exchange beliefs with different religious groups. Tolerance here is in the sense of mu'amalah (social interaction), so that there are common boundaries that may and may not be violated.